A Hybrid Flipped-Classroom Approach for Online Teaching (Journal of the College of Basic Education, 2023)
A teaching strategy known as the hybrid flipped classroom approach mixes traditional face-to-face instruction with online learning activities. In this method, before attending in-person sessions, students learn online using pre-recorded lectures, videos, and other multimedia assets. This gives students the freedom to finish self-paced learning assignments whenever it is convenient for them while simultaneously allowing them to participate in lively conversations and lectures during in-person classes.The hybrid flipped classroom model is gaining popularity as more teachers look for ways to incorporate technology into their lessons and change with the times. The hybrid flipped classroom method offers the advantages of both face-to-face training and online learning in the age of distance learning.Online learning activities include reading materials, interactive tests, audio files, and peer-reviewed assignments when using the hybrid flipped classroom technique. Students' interest and engagement in the learning process can be raised by using online learning activities to teach them how to learn independently.When students attend classes in person, teachers can concentrate on experiential learning activities like group discussions and project-based work in addition to giving feedback and help to those who may have had difficulties with online learning. Combining the two methods enables students to benefit from a deeper and more well-rounded educational experience that makes the most of online and face-to-face instruction.Overall, the hybrid flipped classroom approach is a powerful tool for educators to provide enhanced learning experiences to students, particularly in online learning environments. It provides a flexible, adaptable, and personalized way of learning that engages and motivates students, and prepares them for the changing landscape of the 21st-century workforce.